1999
DOI: 10.4269/ajtmh.1999.60.822
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Schistosoma mansoni infection in upper Egypt: the Giza governorate.

Abstract: Abstract. We found an unexpectedly high prevalence of Schistosoma mansoni in a village in the Upper Egyptian governorate of Giza. Historically, S. mansoni is endemic in the northern Egyptian Nile Delta rather than in the southern Upper Egypt. This observation was made during an evaluation of a rural health care schistosomiasis surveillance program using a cross sectional survey for S. haematobium and S. mansoni in the village of El-Gezira El-Shakra ElSaf district in the Upper Egypt Giza Governorate. A 10% syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
5
7
0
Order By: Relevance
“…S. mansoni was rare being consequential in Fayoum only, which had a prevalence of 4.3% [23,32,33] . Although this survey did not include Giza, yet another study carried out in one of the villages of this governorate indicated that the estimated prevalence of S. haematobium was 7.4% which was in accord with the results of other areas of Middle and Upper Egypt [34–36] . On the other hand, the prevalence of S. mansoni was unusually high amongst the villagers (33.7%) and exceptionally high amongst the primary school children (57.7%) of the same village [36] .…”
Section: Trend Of Schistosomiasis In Egyptsupporting
confidence: 77%
See 2 more Smart Citations
“…S. mansoni was rare being consequential in Fayoum only, which had a prevalence of 4.3% [23,32,33] . Although this survey did not include Giza, yet another study carried out in one of the villages of this governorate indicated that the estimated prevalence of S. haematobium was 7.4% which was in accord with the results of other areas of Middle and Upper Egypt [34–36] . On the other hand, the prevalence of S. mansoni was unusually high amongst the villagers (33.7%) and exceptionally high amongst the primary school children (57.7%) of the same village [36] .…”
Section: Trend Of Schistosomiasis In Egyptsupporting
confidence: 77%
“…Although this survey did not include Giza, yet another study carried out in one of the villages of this governorate indicated that the estimated prevalence of S. haematobium was 7.4% which was in accord with the results of other areas of Middle and Upper Egypt [34–36] . On the other hand, the prevalence of S. mansoni was unusually high amongst the villagers (33.7%) and exceptionally high amongst the primary school children (57.7%) of the same village [36] . In conclusion, the study of the nine governorates of Egypt confirmed the already documented change in the pattern of transmission of both species of schistosome infection in Upper and Lower Egypt [22] .…”
Section: Trend Of Schistosomiasis In Egyptsupporting
confidence: 77%
See 1 more Smart Citation
“…11 The study area can be considered a new focus of S. mansoni because all control programs were concerned mainly with S. haematobium, which is less prevalent than S. mansoni. 10 The cure rate in this study for Mirazid-treated household members and school children was 8.9% and 9.1%, respectively. Irrespective of the type of treatment, all cured school children and most of the cured household members had light infections.…”
Section: Discussionmentioning
confidence: 51%
“…It is relatively near the Theodor Bilharz Research Institute, and is a focus of S. mansoni infection. 10 The study was conducted in collaboration with the MOHP.…”
Section: Methodsmentioning
confidence: 99%